2019
DOI: 10.1002/hep.30235
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Natural Killer Cell NKp30‐Mediated Function and Altered NCR3 Splice Variants in Hepatocellular Carcinoma

Abstract: these findings provide evidence in support of a role of NKp30 and its major ligand in HCC development and evolution. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 48 publications
(140 reference statements)
4
69
0
Order By: Relevance
“…[60][61][62] Elevated preoperative peripheral blood neutrophil-to-lymphocyte (NLR) ratio is also a poor prognostic factor for intrahepatic and extrahepatic CCA, [63][64][65][66] as well as in patients with advanced CCA undergoing chemotherapy. 67 73,74 Furthermore, immunotherapy with infusion of activated allogeneic NK cells has also been performed in HCC patients with promising outcomes. 75,76 However, before such treatments can be employed in CCA, it is necessary to determine if NK cells have the capacity to infiltrate CCA, which NK cell receptor-ligand interactions are important for recognition of CCA, and how NK cells are affected by evasion strategies employed by the tumour and its microenvironment.…”
Section: The Role Of the Innate Immune Sys Tem In CC Amentioning
confidence: 99%
“…[60][61][62] Elevated preoperative peripheral blood neutrophil-to-lymphocyte (NLR) ratio is also a poor prognostic factor for intrahepatic and extrahepatic CCA, [63][64][65][66] as well as in patients with advanced CCA undergoing chemotherapy. 67 73,74 Furthermore, immunotherapy with infusion of activated allogeneic NK cells has also been performed in HCC patients with promising outcomes. 75,76 However, before such treatments can be employed in CCA, it is necessary to determine if NK cells have the capacity to infiltrate CCA, which NK cell receptor-ligand interactions are important for recognition of CCA, and how NK cells are affected by evasion strategies employed by the tumour and its microenvironment.…”
Section: The Role Of the Innate Immune Sys Tem In CC Amentioning
confidence: 99%
“…Other studies point to additional receptor-ligand axes, such as the DNAX Accessory Molecule-1 (DNAM-1) activating NKR and its ligand CD155, in HCC development [5]. Our recently published data point to an altered expression and function of the NKp30 activating receptor in circulating and resident NK cells of HCC patients, the former expressing an inappropriately high level of the Tim-3 exhaustion marker [6]. This, together with decreased expression of the major NKp30 ligand B7-H6 in liver cancer tissue relative to the stage of the disease suggests that this ligand play a major role in cancer surveillance.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, available evidence showed a positive correlation between the frequency of circulating and intrahepatic NK cells and survival in patients with HCC [4]. Interestingly, HCC cells express ligands of several activating NK receptors (NKR), including NKp30, natural killer receptor group 2, member D (NKG2D) and DNAM-1 such as the B7 protein homolog 6, the major histocompatibility complex class I chain-related protein A and B (MICA/B) and CD155, respectively, whose expression can correlate with the outcome of the disease [5,6]. Despite these findings supporting a role for NK cells in HCC immune surveillance, the pathogenetic mechanisms leading to HCC development and progression are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…B7-H6 expressed by HCC cells was shown to down-modulate activating NKp30 and to increase insoluble form in advanced stages. 28 The abundance of tumour-infiltrating T cells has been related to survival in HCC patients, [29][30][31][32] but anti-tumour T cell response is impaired by tolerance-inducing mechanisms of the TIME. CD8 + and CD4 + T cells are enriched in early HCC and progressively decrease during tumour progression.…”
Section: Effector Cellsmentioning
confidence: 99%
“…A recent study suggested the involvement of NKp30 and its ligand B7 homolog 6 (B7‐H6) in HCC development and evolution. B7‐H6 expressed by HCC cells was shown to down‐modulate activating NKp30 and to increase insoluble form in advanced stages …”
Section: Introductionmentioning
confidence: 99%